2019
DOI: 10.1155/2019/5646143
|View full text |Cite|
|
Sign up to set email alerts
|

A Device Improves Signs and Symptoms of TMD

Abstract: Background. Temporomandibular joint dysfunction (TMD) therapy remains an open challenge for modern dentistry. Herein, we propose a new neuromuscular lingual device able to reduce signs and symptoms of TMD in female patients with chronic orofacial pain. Methods. 50 females with myofascial TMD according to RDC/TMD were randomly assigned to study (n = 25) and control groups (n = 25). At T0, both groups received sEMG/KNG and pain evaluation by the VAS scale. The study group received the ELIBA device (lingual eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…However, here, previous orthodontic treatment did not pose a risk of TMD pain. This is consistent with previous findings that orthodontic treatment produces a stable occlusion, which balances tension among masticatory muscles 32 . Godoy et al 33 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, here, previous orthodontic treatment did not pose a risk of TMD pain. This is consistent with previous findings that orthodontic treatment produces a stable occlusion, which balances tension among masticatory muscles 32 . Godoy et al 33 .…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with previous findings that orthodontic treatment produces a stable occlusion, which balances tension among masticatory muscles. 32 Godoy et al 33 observed that orofacial pain after orthodontic treatment is an adaptive response of the masticatory muscles and usually resolves within a week.…”
Section: Discussionmentioning
confidence: 99%
“…used data from the same clinical trial but investigated different outcomes. In addition, the study of Pietropaoli et al., 28 was revised and republished by Monaco et al 29 . In all these cases, the two or three reports that evaluated the same outcomes were treated as a single RCT for analysis purposes.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the methodology used in the included articles did not influence the results of this review. 29 In all these cases, the two or three reports that evaluated the same outcomes were treated as a single RCT for analysis purposes. Therefore, 106 studies were included in the final synthesis (Figure 1).…”
Section: Risk Of Bias Assessmentmentioning
confidence: 99%
“…In the article titled "A New Device Improves Signs and Symptoms of TMD" [1], we would like to clarify the title, the authorship, the provenance of the device with the International Academy of Posture and Neuromyofascial Occlusion Research (I.A.P.N.O.R. ), and details of the methods.…”
mentioning
confidence: 99%